Rare cause of cystic cerebellopontine angle lesion: Answer. (February 2020) - Singhal, Aparna; Hackney, James R.; Chapman, Philip R.
Highlights: Intracranial neurenteric cysts are rare but can present as extra-axial lesions in the posterior fossa. Malignant change is extremely rare and such lesions show more focal, nodular and heterogeneous enhancement. Most common malignant pathology seen was adenocarcinoma, papillary type.